A Method for Suppressing Torque Ripple of Permanent Magnet Synchronous Motor by Harmonic Injection Considering Loss Constraints - Cao, Jingyun; Zhu, Lihua; Gu, Yuxi; Li, Xiaoning (2024 IEEE 25th China Conference on System Simulation Technology and its Application (CCSSTA), 2024)
Permanent Magnet Synchronous Motor (PMSM) are widely used, but they suffer from torque ripple issues, which can be effectively mitigated through the harmonic injection method of the control strategy. Currently, harmonic injection methods for suppressing torque ripple often compromise the thermal performance of PMSMs, leading to increased losses. Therefore, this paper establishes a model that includes copper loss and iron loss as constraints and proposes a harmonic injection algorithm that incorporates these loss constraints. Furthermore, the motor is simulated and verified at a rated speed of 1200 rpm and an overspeed of 1500 rpm. The results demonstrate that the proposed method can suppress both torque ripple and losses. The torque ripple of the PMSM is reduced by more than 38.86%, the total harmonic distortion (THD) is reduced by approximately 29.01%, and the losses are reduced by more than 30.27%. This method has a small computational complexity and simple implementation. It can reduce losses and improve current waveform while suppressing torque ripple.